The inflective of two aspects from the accusative infinitive with omitted verb in Adur Almason by Alsameen Alhalabi - Taha Ahmed, Jassim (Journal of College of Education, 2020)
The phenomenon of meaning and inflective is a vast field of scientific research in the arabic grammar, and it is not exaggerated if this idea is to be the basic of grammar and the wider field. In this research, the question of grammar guidance for what has been endured in more than inflective, especially the exchange place of the presumption, which was absent from others, and took the idea (accusative infinitive with omitted) and presented it to the directives of the Alsameen Alhalabi in Aldur Almasoon book, so it seems to me as a scientific issue with a graphical and semantic value, Alhalabe has offered several directives to the infinitive in question, and the case and object have come to the fore on other possible grammatical aspects. It was arranged in accordance with the order of Alsur in which the source identified, start by presenting the sayings of the former scientists, to conclude the value of this offer and the extent of perfection that the chubby had in his directions.